The Relationship Between Formula Feeding and Incidence of Diarrhea Among Infants Ages 0-6 Months at Sikumana Public Health Center, Kupang City - Suban, Irenne Sovia Lestari; Amat, Anita Lidesna Shinta; Wardani, Nimas Prita Rahajeningtyas Kusuma; Woda, Rahel Rara (Jurnal Biologi Tropis, 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among infants in Indonesia. Formula feeding is often associated with diarrhea, especially among infants under six months of age. Based on 2024 data from the Kupang City Health Office, Sikumana Public Health Center ranked second in diarrhea cases among children under five, with 1,376 reported cases. This study employed an analytical observational design with a cross-sectional approach. The population included all infants aged 0–6 months residing in the Sikumana Public Health Center area. A total of 120 infants were selected using a consecutive sampling technique according to inclusion and exclusion criteria. Data were collected through structured questionnaires administered to parents and verified with information from the Maternal and Child Health (KIA) book. Data were analyzed using the Chi-square test with a significance level of p<0.05. Among the 120 respondents, 21 infants (17.5%) received formula, while 99 infants (82.5%) did not receive formula. A total of 45 infants (37.5%) experienced diarrhea, and 75 infants (62.5%) did not. Data analysis indicated no meaningful connection between formula feeding and the occurrence of diarrhea (p = 0.352). There was no significant association between formula feeding and the rates of diarrhea in infants aged 0–6 months at the Sikumana Public Health Center located in Kupang City.